The Role of Ferroptosis in Acute Respiratory Distress Syndrome - Qu, Mengdi; Zhang, Hao; Chen, Zhaoyuan; Sun, Xingfeng; Zhu, Shuainan; Nan, Ke; Chen, Wankun; Miao, Changhong (Frontiers in Medicine, 2021)
Ferroptosis is a newly discovered type of regulated cell death that is different from apoptosis, necrosis and autophagy. Ferroptosis is characterized by iron-dependent lipid peroxidation, which induces cell death. Iron, lipid and amino acid metabolism is associated with ferroptosis. Ferroptosis is involved in the pathological development of various diseases, such as neurological diseases and cancer. Recent studies have shown that ferroptosis is also closely related to acute lung injury (ALI)/ acute respiratory distress syndrome (ARDS), suggesting that it can be a novel therapeutic target. This article mainly introduces the metabolic mechanism related to ferroptosis and discusses its role in ALI/ARDS to provide new ideas for the treatment of these diseases.